The apolipoprotein A-I mimetic peptide, D-4F, alleviates ox-LDL-induced oxidative stress and promotes endothelial repair through the eNOS/HO-1 pathway. (April 2017) - Liu, Donghui; Ding, Zhenzhen; Wu, Mengzhang; Xu, Wenqi; Qian, Mingming; Du, Qian; Zhang, Le; Cui, Ye; Zheng, Jianlan; Chang, He; Huang, Caihua; Lin, Donghai; et al.
Abstract: Apolipoprotein A-I (apoA-I) mimetic peptide exerts many anti-atherogenic properties. However, the underlying mechanisms related to the endothelial protective effects remain elusive. In this study, the apoA-I mimetic peptide, D-4F, was used. Proliferation assay, wound healing, and transwell migration experiments showed that D-4F improved the impaired endothelial proliferation and migration resulting from ox-LDL. Endothelial adhesion molecules expression and monocyte adhesion assay demonstrated that D-4F inhibited endothelial inflammation. Caspase-3 activation and TUNEL stain indicated that D-4F reduced endothelial cell apoptosis. A pivotal anti-oxidant enzyme, heme oxygenase-1 (HO-1) was upregulated by D-4F. The Akt/AMPK/eNOS pathways were involved in the expression of HO-1 induced by D-4F. Moreover, the anti-oxidation, pro-proliferation, and pro-migration capacities of D-4F were diminished by the inhibitors of both eNOS (L-NAME) and HO-1 (Znpp). Additionally, downregulation of ATP-binding cassette transporter A1 (ABCA1) by siRNA abolished the activation of Akt, AMPK and eNOS, and reduced the upregulation of HO-1 triggered by D-4F. Furthermore, D-4F promoted the reendothelialization of injured intima in carotid artery injury model of C57BL/6J mice in vivo . In summary, these findings suggested that D-4F might be a powerful candidate in the protection of endothelial cells and the prevention of cardiovascular disease (CVD). Highlights: D-4F upregulated HO-1 expression via Akt/AMPK/eNOS pathway in endothelial cells. D-4F scavenged intracellular ROS through eNOS/HO-1 pathway. D-4F promoted endothelial repair, and improved endothelial function via eNOS/HO-1.